Willingness and concerns of transfusion-dependent hematological patients toward the option of home transfusion therapy. (May 2021) - Barki-Harrington, Liza; Baron-Epel, Orna; Shaulov, Adir; Akria, Luiza; Barshay, Yossef; Dally, Najib; Deshet, Dana; Inbar, Tsofia; Koren-Michowitz, Maya; Leiba, Merav; Moshe, Yakir; Shvidel, Lev; et al.
Background: One of the main obstacles of providing home-based palliative care to transfusion-dependent hematology patients is the lack of home transfusions services. While healthcare professionals are concerned with safety and cost of home transfusions, the attitude of the patients toward home transfusions are mostly unknown. Aim: To obtain quantitative data regarding the willingness and concerns of transfusion-dependent patients with hematological diseases toward the option of home transfusions. Design: A cross sectional survey including a self-administered questionnaire in one of the three main spoken languages in Israel was administered to patients in 17 hospital hematology outpatient clinics between May 2019 and March 2020. Results: About 52% of 385 patients that participated in the survey preferred home transfusions to hospital transfusions. Gender, age, education, or type of disease were not associated with preference for home transfusions, nor were hospital location or its size. The likelihood to prefer home transfusions was significantly higher among the Hebrew-speakers and those who had not experienced adverse effects previously. The most significant factor associated with preference of home transfusions was a perceived negative effect of hospital-based transfusion on quality of life. The main reason to reject home transfusions was fear of possible adverse effects and concerns over losing contact with the medical staff at the treating hospital. Conclusion: These data suggest that a significant portion of transfusion-dependent patients in Israel view home transfusions as a preferred treatment option and that its successful implementation requires maintaining ongoing contact with the treating hospital.